Caveolin-1 promotes radioresistance in rhabdomyosarcoma through increased oxidative stress protection and DNA repair. (1st May 2021) - Codenotti, Silvia; Marampon, Francesco; Triggiani, Luca; Bonù, Marco Lorenzo; Magrini, Stefano Maria; Ceccaroli, Paola; Guescini, Michele; Gastaldello, Stefano; Tombolini, Vincenzo; Poliani, Pietro Luigi; Asperti, Michela; Poli, Maura; et al.
Abstract: The aim of this work was to investigate whether Caveolin-1 (Cav-1), a membrane scaffolding protein widely implicated in cancer, may play a role in radiation response in rhabdomyosarcoma (RMS), a pediatric soft tissue tumor. For this purpose, we employed human RD cells in which Cav-1 expression was stably increased via gene transfection. After radiation treatment, we observed that Cav-1 limited cell cycle arrest in the G2/M phase and enhanced resistance to cell senescence and apoptosis via reduction of p21 Cip1/Waf1, p16 INK4a and Caspase-3 cleavage. After radiotherapy, Cav-1-mediated cell radioresistance was characterized by low accumulation of H2AX foci, as confirmed by Comet assay, marked neutralization of reactive oxygen species (ROS) and enhanced DNA repair via activation of ATM, Ku70/80 complex and DNA-PK. We found that Cav-1-overexpressing RD cells, already under basal conditions, had higher glutathione (GSH) content and greater catalase expression, which conferred protection against acute treatment with hydrogen peroxide. Furthermore, pre-treatment of Cav-1-overexpressing cells with PP2 or LY294002 compounds restored the sensitivity to radiation treatment, indicating a role for Src-kinases and Akt pathways in Cav-1-mediated radioresistance. These findings were confirmed using radioresistant RD and RH30 lines generated by hypofractionated radiotherapy protocol, which showed marked increase of Cav-1, catalase and Akt, and sensitivity to PP2 and LY294002 treatment. In conclusion, these data suggest that concerted activity of Cav-1 and catalase, in cooperation with activation of Src-kinase and Akt pathways, may represent a network of vital mechanisms that allow irradiated RMS cells to evade cell death induced by oxidative stress and DNA damage. Highlights: Cav-1 promoted RD cell survival after irradiation. Cav-1 protected against cell senescence and apoptosis. Cav-1 diminished oxidative stress and increased catalase expression. Cav-1 enhanced DNA repair. Src-kinase and Akt inhibition prevented radioresistance.